2010
DOI: 10.1016/j.micinf.2010.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression changes in the host response between resistant and susceptible inbred mouse strains after influenza A infection

Abstract: Inbred mouse strains exhibit differences in susceptibility to influenza A infections. However, the molecular mechanisms underlying these differences are unknown. Therefore, we infected a highly susceptible mouse strain (DBA/2J) and a resistant strain (C57BL/6J) with influenza A H1N1 (PR8) and performed genome-wide expression analysis. We found genes expressed in lung epithelium that were specifically downregulated in DBA/2J mice, whereas a cluster of genes on chromosome 3 was only down-regulated in C57BL/6J. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 51 publications
3
61
0
Order By: Relevance
“…1B) was analyzed. This result is consistent with recently published work that has evaluated differences in the pathogenicity of H1N1 and other influenza viruses in inbred mice (1,6,58).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…1B) was analyzed. This result is consistent with recently published work that has evaluated differences in the pathogenicity of H1N1 and other influenza viruses in inbred mice (1,6,58).…”
Section: Resultssupporting
confidence: 93%
“…First, our studies revealed that different inbred mouse strains are differentially susceptible to the pathological consequences of infection with the H1N1 strain of the virus: A/J mice are more susceptible than BALB/c and C57BL/10 mice (not shown). Other studies have shown that the mouse genetic background can dramatically impact susceptibility to influenza A virus strains (1,6,7,58). In one particularly systematic study of protective immunity to A/Puerto Rico/8/34 (A/PR8) (58), a mouse-adapted laboratory strain of influenza virus, A/J and DBA/2 mice displayed the most susceptibility to infection, while C57BL/6, BALB/c, CBA, and FVB/NJ mice were among the more resistant strains and ultimately recovered from infection.…”
Section: Discussionmentioning
confidence: 99%
“…A similar conclusion was drawn in a recent study with influenza A virus infection in mice [50]. Nonetheless, our data emphasize the overall complexity of the processes involved, which can be attributed to the participation of many differentially expressed gene products in the anti-inflammatory regulatory circuits.…”
Section: Discussionsupporting
confidence: 91%
“…West Nile virus strain IS-98-ST1 was isolated from a white stork in Israel; it is highly neuroinvasive in adult mice (21). A/Puerto Rico/8/34 (H1N1) PR8 FR 0807 influenza virus is a mouse-adapted strain (22,23). Viral stocks were produced under biosafety level 3 conditions.…”
Section: Mice Cells and Virusmentioning
confidence: 99%